Trimethyl Chitosan Improves Anti-HIV Effects of Atripla as a New Nanoformulated Drug - Shohani, Sepideh; Mondanizadeh, Mahdieh; Abdoli, Asghar; Khansarinejad, Behzad; Salimi-Asl, Mohammad; Shafiee Ardestani, Mehdi; Ghanbari, Maryam; Sadeghi Haj, Mehrdad; Zabihollahi, Rezvan (Current HIV Research, 2017)
Background: Highly active antiretroviral therapy (HAART) has been commonly used for HIV treatment. Its main drawbacks like drug resistance and side effects raised researcher’s interest to find new approaches for its treatment. Trimethyl chitosan is one of the drug carriers which has been introduced recently. Materials and Methods: the conjugated atripla-trimethyl chitosan was designed and characterized by zetasizer, AFM and FTIR techniques. The drug conjugation with trimethyl chitosan and cellular uptake of nano-conjugate were determined by spectrophotometry. XTT test was used to measure the cytotoxicity. Anti-retroviral efficiency was studied by ELISA test. Results: Zetasizer Results proved that the average size of nano-conjugate particles agglomeration was 493.4±24.6 nm but the size of the majority of the particles was 177.2±7.8 nm with the intensity of 87.9%. AFM technique revealed that the sizes of nano-conjugate and trimethyl chitosan were 129 nm and 59.78 nm, respectively. Zeta potential was -1.35±0.04 mv for nano-conjugate and -7.69±0.3 mv for drug. Conjugation efficiency of atripla with trimethyl chitosan was 5.27%. Measured cellular uptake with spectrophotometry for nano-conjugate was about twice of the free drug in examined concentrations (P=0.007). Compared to atripla, the nano-conjugate showed a higher inhibitory effect on HIV replication (P=0.0001). Conclusion: The result showed that atripla-TMC conjugate does not have a significant cytotoxicity effect. Due to the higher inhibitory effect of nano-conjugate on viral replication, it can be used in lower concentration for antiviral treatment, which resulted in reduction of drug resistance and other side effects.
Keywords: Chitosan